Penguatan Konstitusi dan Ideologi Kebangsaan Demi Mewujudkan Perdamaian di Indonesia - Budiman N.P.D Sinaga (PAX HUMANA, 2015)
The nature of the nation could not be separated from the purpose of the nation it self. The purpose of the nation is a purpose that want to be achieved by a nation.This purpose is the major reason for establishing the state of national founder. Thus, nature of national is the purpose of Indonesian people. The purpose of a nation must be consistent with the fact that inherent in the nation. For example, one of the statement attached to the people of Indonesia is unity in diversity. Therefore, the founders of the Indonesian state was deliberately adjust the national with the nation of Indonesian people. The purpose of the nation included in the constitution in order enforceable. The purpose of the nation had been included in the 1945 Constitution of the Republic of Indonesia. Indonesia's major problems such as separatism, sectarianism and terrorism should be studied constitutionally. Some of the problems is possible that there is a problem in the past and have been resolved through an agreement set forth in the Constitution. And the Problems such as these should be resolved by constitutionally approachKeywords: The purpose of the nation , Constitution, Constitutional.